Field-induced charge separation dynamics in monolayer MoS2. (24th July 2017) - Vella, Daniele; Ovchinnikov, Dmitry; Viola, Daniele; Dumcenco, Dumitru; Kung, Yen C; Pogna, Eva A A; Conte, Stefano Dal; Vega-Mayoral, Victor; Borzda, Tetiana; Prijatelj, Matej; Mihailovic, Dragan; Kis, Andras; et al.
Abstract: The absorption spectra of 2D semiconductors are dominated by excitons with binding energy of several hundreds of meV. Nevertheless, even single layers show an appreciable photovoltaic effect and work as the active material in high sensitivity photodetectors, thus indicating some degree of free charge carrier photogeneration. Here, we perform ultrafast transient absorption spectroscopy on monolayer MoS2 in a field-effect transistor configuration. We show that even a moderate in-plane electric field of a few kV cm −1 can significantly increase the yield of charge carriers from photogenerated hot electron–hole pairs.